Police work and new 'security devices': A tale from the beat. (August 2015) - Tanner, Samuel; Meyer, Michaël
Mobile technologies have brought about major changes in police equipment and police work. If a utopian narrative remains strongly linked to the adoption of new technologies, often formulated as 'magic bullets' to real occupational problems, there are important tensions between their 'imagined' outcomes and the (unexpected) effects that accompany their daily 'practical' use by police officers. This article offers an analysis of police officers' perceptions and interactions with security devices. In so doing, it develops a conceptual typology of strategies for coping with new technology inspired by Le Bourhis and Lascoumes: challenging, neutralizing and diverting. To that purpose, we adopt an ethnographic approach that focuses on the discourses, practices and actions of police officers in relation to three security devices: the mobile digital terminal, the mobile phone and the body camera. Based on a case study of a North American municipal police department, the article addresses how these technological devices are perceived and experienced by police officers on the beat.